2021
DOI: 10.1002/celc.202001352
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Morphologically Controlled Synthesis of Polyphosphazenes for Electrochemical Applications

Abstract: Polyphosphazenes (PPNs) belong to organic‐inorganic hybrid polymeric skeletal materials suitably fabricated via precipitation or condensation polymerization and self‐assembly approaches. Organic moieties with two and three −NH2 or −OH functionalities inherit subsequent ordered 2D and 3D arrangements of the atoms and molecules to attain the morphologies such as nanotubes, nano/micro‐spheres, fibers, nanosheets, and covalent organic frameworks (COFs). Auto‐doping is a strategic feature of PPN materials to origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…In recent days, carbon materials have attracted the attention of researchers. In particular, porous carbon materials possess a good pore volume with high surface area, extraordinary mechanical stability with less density, and excellent surface permeability with chemical inertness. These highly noteworthy morphological and structural properties make porous materials very suitable candidates for adsorbents, storage materials, catalyst supports, supercapacitors, and sensors and in solar cells and fuel cells to act as an electrocatalyst for the oxygen evolution reaction (OER), hydrogen evolution reaction (HER), and oxygen reduction reaction (ORR). , The cyclopolyphosphazene material pyrolysis has improved their morphological properties from being even on the surface to porous, rigid solid, to hollow and from traditional PN ̵bond to̵ C–C ̵graphitic bond networks in nature . Dufek and co-workers synthesized the PZS and carbonized them at 1000 °C to form porous carbon materials and used lithium ion electrodes which exhibited the stable capacity of 1200 mAh g –1 , with almost 95% retention after 40 cycles …”
Section: Applications Of the Cyclomatrix Type Of Polyphosphazenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent days, carbon materials have attracted the attention of researchers. In particular, porous carbon materials possess a good pore volume with high surface area, extraordinary mechanical stability with less density, and excellent surface permeability with chemical inertness. These highly noteworthy morphological and structural properties make porous materials very suitable candidates for adsorbents, storage materials, catalyst supports, supercapacitors, and sensors and in solar cells and fuel cells to act as an electrocatalyst for the oxygen evolution reaction (OER), hydrogen evolution reaction (HER), and oxygen reduction reaction (ORR). , The cyclopolyphosphazene material pyrolysis has improved their morphological properties from being even on the surface to porous, rigid solid, to hollow and from traditional PN ̵bond to̵ C–C ̵graphitic bond networks in nature . Dufek and co-workers synthesized the PZS and carbonized them at 1000 °C to form porous carbon materials and used lithium ion electrodes which exhibited the stable capacity of 1200 mAh g –1 , with almost 95% retention after 40 cycles …”
Section: Applications Of the Cyclomatrix Type Of Polyphosphazenesmentioning
confidence: 99%
“…Polyphosphazenes contain a wide range of potential applications from fire retardants to fibers of optical materials, , fuel cells, elastomers via films and coatings, composites and carbon materials, a variety of different membranes, electro-optical to biomedical materials, as well as solid battery electrolytes . In the context of this review, this is necessary to study the history of polyphosphazene development over the years before going on to the actual study of polyphosphazene related to our research interest.…”
Section: Introductionmentioning
confidence: 99%
“…These hybrid materials comprise unsaturated rings of alternating phosphor and nitrogen atoms that are covalently connected via diphenyl oxide bridges. The organic phase monomer used in the IP process is hexachlorocyclotriphosphazene (HCCP), a versatile building block for making polyphosphazene-based materials via reactions with a broad range of nucleophiles. , The cyclic phosphazene group offers extraordinary intrinsic properties, such as natural flame retardancy and thermal stability . Most of the preparation methods involving HCCP are based on solution polymerization, and only a few studies have been dedicated to synthesizing polyphosphazene films with IP. , Maaskant et al reported that the interfacial polycondensation of HCCP with diphenols in conventional IP is too slow to allow for ultrathin (∼10 8 m) film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the polymerization and substitution of the reactive chlorine atoms, they give rise to a wide variety of new polyphosphazenes, containing from 100 to 15,000 or more repeating units (with molecular weights ranging from 2 to 10 × 10 6 Da) with an unusually broad range of useful properties. Polyphosphazenes with elastomeric [ 18 , 19 ], optical [ 20 ], proton-conducting [ 21 ], electrochemical [ 22 ], and fire-resistant [ 23 ] properties have been investigated and applied in the development of membranes [ 24 ], fuel cells [ 25 ], and hybrid materials [ 12 ]. New elastomeric inorganic silicon-based compounds, and specifically fire-resistant elastomers and plastics, have been studied for military purposes [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%